Subdural Empyema Complicating Bacterial Meningitis: A Challenging Diagnosis in a Patient with Polysubstance Abuse - Melissa Dakkak; William Russell Cullinane; Virin Rajiv Neil Ramoutar (Case Reports in Medicine)
Subdural empyema (SDE) and cerebrovascular accident (CVA) are uncommon life-threatening complications of bacterial meningitis, which require urgent neurosurgical intervention to prevent adverse outcomes. Clinicians must be vigilant of the onset of focal neurologic deficits or seizure activity to establish the diagnosis of SDE. Streptococcus pneumoniae accounts for <1% of pyogenic brain abscesses. This case describes a presentation of community acquired pneumococcal pneumonia in which the diagnosis of SDE with vasculitis induced CVA was confounded by concomitant substance abuse and sedation.